2020
DOI: 10.1186/s12943-020-01224-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of N6-methyladenosine (m6A) modification in the regulation of circRNAs

Abstract: N 6-methyladenosine (m 6 A), the most abundant modification in eukaryotic cells, regulates RNA transcription, processing, splicing, degradation, and translation. Circular RNA (circRNA) is a class of covalently closed RNA molecules characterized by universality, diversity, stability and conservatism of evolution. Accumulating evidence shows that both m 6 A modification and circRNAs participate in the pathogenesis of multiple diseases, such as cancers, neurological diseases, autoimmune diseases, and infertility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
185
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(186 citation statements)
references
References 111 publications
(171 reference statements)
1
185
0
Order By: Relevance
“…As a primary component of the m6A methyltransferase complex, KIAA1429 has recently been demonstrated to promote HCC progression [11,12]. More importantly, growing evidence suggested that the biogenesis and function of circRNAs could be regulated by m6A modi cation and m6A regulated-circRNAs may provide potential therapeutic targets [17,18]. In our present work, we identi ed circDLC1 as a novel KIAA1429-regulated circRNA, which was clinically relevant to favorable prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…As a primary component of the m6A methyltransferase complex, KIAA1429 has recently been demonstrated to promote HCC progression [11,12]. More importantly, growing evidence suggested that the biogenesis and function of circRNAs could be regulated by m6A modi cation and m6A regulated-circRNAs may provide potential therapeutic targets [17,18]. In our present work, we identi ed circDLC1 as a novel KIAA1429-regulated circRNA, which was clinically relevant to favorable prognosis of HCC patients.…”
Section: Discussionmentioning
confidence: 63%
“…The main function of circRNAs in tumor is sponging microRNAs (miRNAs), encoding protein or binding protein (14)(15)(16). Interestingly, more recent studies revealed that methyltransferase-like-3 (METTL3), core complex of methyltransferase, is involved in circRNA biogenesis and function by regulating m6A modi cation (17,18). Thus, the speci c roles of KIAA1429 in mediating circRNAs pathway are urgently needed to explore.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that m6A modification is misregulated in human cancers and may be ideal targets of cancer therapy (Barbieri and Kouzarides, 2020). The m6A modification affects the pathogenesis of multiple diseases and cancers, not only by affecting coding RNAs but also by affecting non-coding RNAs, such as microRNAs, lncRNAs and circRNAs (Fazi and Fatica, 2019;Zhang et al, 2020).…”
Section: M6a Processes and Their Functionsmentioning
confidence: 99%
“…The m6A modification influences the downstream pathways by regulating the fate of an RNA transcript, processing, splicing, degradation, or translation, whether mRNA or non-coding RNA( Fazi and Fatica, 2019 ; Zhang et al, 2020 ). It plays an important role in various biological processes at different levels of the m6A modification of RNA, such as circadian clock ( Fustin et al, 2013 , 2018 ; Zhong et al, 2018 ), DNA damage response ( Xiang et al, 2017 ; Zlotorynski, 2017 ), neural function regulation ( Poeck et al, 2016 ; Zhang F. et al, 2017 ), drosophila sex determination ( Haussmann et al, 2016 ; Poeck et al, 2016 ), and embryonic development ( Kwon et al, 2019 ).…”
Section: M6a Processes and Their Functionsmentioning
confidence: 99%
“…The circGSK3B was highly expressed in HCC tissues, and positively associated with HCC tumor size and vascular invasion. Most circRNAs are formed in the nucleus, however, m 6 A modification promotes the cytoplasmic output of circRNAs (38). Thus, the regulation mechanism of circGSK3B cytoplasmic output including m 6 A modification needs to be further studied.…”
Section: Discussionmentioning
confidence: 99%